Analysis of Florida high school athlete's sports injury data for 2008–2009. (1st March 2011) - Liller, K D; Morris, B; Konin, J; Jang, S; Wong, S; Thorson, S
Abstract : Purpose: To analyze the Florida high school athletes sports injury data for the 2008–2009 academic year and to provide recommendations for further research and practice. The data collected for this study were part of the initiatives of the SMART Institute of the University of South Florida. The surveillance tool is unique in that no other instrument captures the incidence, prevalence, risk factor and exposure information of all sports played by Florida high school athletes. Methods: Certified Athletic Trainers (ATCs) hired by SMART and placed in 10 public high schools in west-central Florida collected the athletes injury and treatment data utilizing the Simtrak software template. Data were collected on football, baseball, volleyball, swimming, track, cross-country, flag football, soccer, basketball, golf, wresting, softball, tennis and cheerleading. Results: Six-hundred injuries were reported by the ATCs. The leading rate of sports-related injury per 1000 athlete-exposures for practices was for football at 3.58, followed by flag football at 2.67 and wrestling at 2.52. For competitions, the leading rate was for football at 19.20, followed by women's soccer at 7.53 and wrestling at 6.59. Flag football emerged as great risk for injury rates in practice and baseball injuries ranked third in frequency. Sprains and strains were the leading physiologic injuries and the leading body sites injured were the ankles, knees and head. Conclusions: These results allow for the development of targeted injury interventions for these athletes leading to reductions in injuries.